Plasma spraying of Al2O3‑Al composite coatings - I. V. Rafalski; A. D. Rulenkov; O. G. Devoino (Литьë и металлургия, 2023)
The article presents the results of modeling and analysis of thermal processes during plasma spraying of Al2O3–Al composite coatings. Modeling was carried out for composite particles with spherical symmetry, taking into account the influence of phase transitions during the melting and evaporation of dissimilar materials in the aluminum‑aluminum oxide system and various particle sizes based on a mathematical model of non‑stationary thermal conductivity, taking into account internal heat sources during phase transitions. The results of studies of the microstructure of composite coatings after plasma spraying of Al2O3–Al based powders, synthesized during metallurgical processing of aluminum matrix quartz‑containing compositions, are presented.